KOMPETENSI GURU AGAMA DALAM MERANCANG DAN MELAKSANAKAN PEMBELAJARAN DI MA DAN MTs AL-AZIZIYAH GUNUNGSARI LOBAR - Natsir, M (JURNAL PENELITIAN KEISLAMAN, 2014)
The Law Number 20 in 2003 about Indonesian education system, the definition of teacher is a professional who plans and carries out a good teaching and learning process. However, during the implementation not all of the teachers do as good as the law and the people have been expected, especially in preparing and making the lesson plan. In order to justify this phenomenon, this research is carried out and this research also applies qualitative descriptive research method. This research shows that first, the competence level of Islam religion teachers (fiqh, Aqidah â Akhlak, Qurâan Hadith, History of Islamic Culture and Arabics) both in Madrasa Aliyah and Madrasa Tsanawiyah in Pondok Pesantren Al âAziziyah Gunung Sari is quite low. Second, the lack of teachersâ ability in designing and making teaching and learning process is an impact of teachersâ understanding and skill in designing and carrying out teaching and learning process in the classroom. Such conditions are the implication of less teachersâ improvisation due to the lack of training and teaching skill improvement.